Conserved features of recombination control in vertebrates. - Linda Odenthal-Hesse (PLoS Biology)
A recent study in PLOS Biology on the epigenetic recombination regulator PRDM9 in salmonid fish reveals that its function has been preserved across vertebrates for hundreds of millions of years, with rapidly evolving DNA-binding domains being a defining attribute.